Constitutive crosspresentation of tissue antigens by dendritic cells controls CD8+ T cell tolerance in vivo. - Luckashenak, N; Schroeder, S; Endt, K; Schmidt, D; Mahnke, K; Bachmann, M; Marconi, P; Deeg, C; Brocker, T (2008)
Immature dendritic cells (DCs) sample tissue-specific antigens (TSAs) and process them for "crosspresentation" via major histocompatibility complex (MHC) class I and II molecules. Findings with adoptively transferred T cell receptor (TCR)-transgenic CD8+ T cells in transgenic mice expressing model TSA indicate that this process contributes to tolerance induction of CD8+ T cells, a phenomenon termed "crosstolerance." However, up to now it has been unknown whether "crosstolerance" can also control autoimmune T cells specific for physiological nontransgenic TSA. Here, we showed that a DC-specific deficiency in uptake of apoptotic material inhibits crosspresentation in vivo. This defect allowed the accumulation of fully functional autoreactive CD8+ T cells that could be activated for autoimmune attack in peripheral lymphoid organs. Thus, our data demonstrate the importance of crosstolerance induction by DCs as a vital instrument for controlling self-reactive T cells from the peripheral repertoire and preventing autoimmune disease.